Reporte de un caso de miocarditis, presumiblemente urliana. Revisión de la literatura. - Durán Álvarez, Sandalio; Casanova Arzola, Ramón; López Benítez, Julio; Más Lago, Pedro (Revista Cubana de Pediatría, 2023)
Presentación de caso.